1995
DOI: 10.1677/joe.0.1450513
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor stimulates cell proliferation and inhibits iodide uptake of FRTL-5 cells in vitro

Abstract: In accordance with the available data most authors conclude that epidermal growth factor (EGF) has very little or no effect on FRTL-5 cells. This has been viewed as a serious handicap of this cell line. In the present study we cultivated three strains of FRTL-5 cells from different sources and assessed their response to EGF with regard to proliferation, function and differentiation. Cell proliferation was assessed by counting in a Coulter cell counter after culturing cells at suboptimal conditions in well plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…Despite the fact that FRTL-5 cells have been extensively used for many years, the mechanism regulating their (23). It should be pointed out that an EGF effect has been described mainly in aged cells; this could indeed be the case in the current investigation, as commented upon below.…”
Section: Discussionmentioning
confidence: 65%
“…Despite the fact that FRTL-5 cells have been extensively used for many years, the mechanism regulating their (23). It should be pointed out that an EGF effect has been described mainly in aged cells; this could indeed be the case in the current investigation, as commented upon below.…”
Section: Discussionmentioning
confidence: 65%
“…The differential expression of these critical genes and their downstream effectors enables cells to override growth controls and eventually undergo carcinogenesis. Mutations of p53 [3], RAS [4], and B-RAF [5], rearrangement of PPARG [6] and RET/PTC [7], and amplification and overexpression of FGFR and EGFR [8] have been observed in thyroid cancer. However, the precise mechanisms of thyroid cancer at the molecular level are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…many studies have reported on the regulation of thyroid cell proliferation by TSh [9], insulin/insulinlike growth factor i (iGF-i) [10,11], and other growth factors, including fibroblast growth factor-2 (FGF-2) [12] and epidermal growth factor [13]. These studies were conducted by using various cell culture systems, such as primary cultures of rat, dog, sheep and human thyroid cells as well as using rat thyroid cell lines, such as FRTL-5, WRT, and Pc cl3.…”
Section: Preparation and Primary Culture Of Porcine Thyroid Epitheliamentioning
confidence: 99%